Clinical and Epidemiological Aspects of Multiple Sclerosis in Children - NASEHI, Mohammad Mehdi; SAHRAIAN, Mohammad Ali; NASER MOGHADDAS, Abdorreza; GHOFRANI, Mohammad; ASHTARI, Fereshteh; TAGHDIRI, Mohammad Mahdi; TONEKABONI, Seyed Hassan; KARIMZADEH, Parvaneh; AFSHARI, Mahdi; MOOSAZADEH, Mahmood (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Nasehi MM, Sahraian MA, Naser Moghaddasi A, Ghofrani M, Ashtari F, Taghdiri MM, Tonekaboni SH, Karimzadeh P, Afshari M, Moosazadeh M. Clinical and Epidemiological Aspects of Multiple Sclerosis in Children. Iran J Child Neurol. Spring 2017; 11(2):37-43. Abstract Objective Overall, 2%-5% of patients with multiple sclerosis (MS) experienced the first episode of disease before the age 18 years old. Since the age of onset among children is not similar to that in general population, clinicians often fail to early diagnose the disease. This study aimed to determine the epidemiological and clinical patterns of MS among Iranian children. Materials & Methods In this cross-sectional study carried out in Iran in 2014-2015, information was collected using a checklist with approved reliability and validity. Method sampling was consensus. Data were analyzed using frequency, mean and standard deviation indices by means of SPSS ver. 20 software. Results Totally, 177 MS children were investigated. 75.7% of them were female. Mean (SD), minimum and maximum age of subjects were 15.9 (2), 7 and 18 yr, respectively. The most reported symptoms were sensory (28.2%), motor (29.4%), diplopia (20.3%) and visual (32.8%). Primary MRI results showed 91.5% and 53.1% periventricular and spinal cord lesions, respectively. Conclusion MS is significantly more common among women. The most common age of onset is during the second decades. Sensory and motor problems are the most symptoms, while, periventricular and spinal cord lesions are the most MRI results. References 1. Ascherio A, Munger K. Epidemiology of multiple sclerosis: from risk factors to prevention. Semin Neurol 2008; 28(1): 17-28. 2. Abedidni M, Habibi Saravi R, Zarvani A, Farahmand M. Epidemiologic study of multiple sclerosis in Mazandaran,Iran, 2007. J Mazandaran Univ Med Sci 2008; 18(66): 82-6. 3. Taghdiri MM, Gofrani M, Barzegar M, Moayyedi A, Tonekaboni H. The survey of 20 cases of multiple sclerosis in children in mofid hospital of Tehran. J Rehabil, 2001; 4(6-7):61-67. 4. Benito-Leon J, Martinez P. Health-related quality of life in multiple sclerosis. Neurologia 2003; 18: 207-10. 5. Nedjat S, Montazeri A, Mohammad K, Majdzadeh R, Nabavi N, Nedjat F, et al . Quality of Life in Multiple Sclerosis Compared to the Healthy Population in Tehran. Iran J Epidemiol 2006; 2 (3 and 4) :19-24. 6. Marrie RA. Environmental risk factors in multiple sclerosis aetiology. Lancet Neurol 2004; 3(12):709-18. 7. Milo R, Kahana E. Multiple sclerosis:geoepidemiology, genetics and the environment. Autoimmun Rev 2010; 9(5): A387-A394. 8. Banwell B, Ghezzi A, Bar-Or A, Mikaeloff Y. Multiple sclerosis in children: clinical diagnosis, therapeutic strategies, and future directions. The Lancet Neurol, 2007;6(10):887-902. 9. Ebers GC. Environmental factors and multiple sclerosis. The Lancet Neurol, 2008;7(3):268-277. 10. Noseworthy JH, Lucchinetti C, Rodriguez M, Weinshenker BG. Multiple Sclerosis. N Engl J Med 2000; 343(13):938-52. 11. Rudick RA, Cohen JA, Weinstock-Guttman B, Kinkel RP, Ransohoff RM. Management of multiple sclerosis. N Engl J Med 1997: 337(22): 1604-11. 12. Greer JM, McCombe PA. Role of gender in multiple sclerosis: clinical effects and potential molecular mechanisms. J Neuroimmunol 2011;234(1-2): 7-18. 13. Boiko A, Vorobeychik G, Paty D, Devonshire V, Sadovnick D. Early onset multiple sclerosis A longitudinal study. Neurology 2002; 59(7):1006-1010. 14. . Ashtari F, Shaygannejad V, Heidari F, Akbari M. Prevalence of Familial Multiple Sclerosis in Isfahan, Iran. Journal of Isfahan Medical School, 2011;29(138.2):555- 561. 15. Mazaheri S, Fazlian M, Hossein Zadeh A. Clinical and Epidemiological Features of Early and Adult Onset Multiple Sclerosis in Hamedan, Iran, 2004–2005. Yafteh 2008; 9 (4) :39-44. 16. Saman-Nezhad B, Rezaee T, Bostani A, Najafi F, Aghaei A. Epidemiological Characteristics of Patients with Multiple Sclerosis in Kermanshah, Iran in 2012. J Mazand Univ Med Sci 2013; 23(104): 97-101 (In Persian). 17. Renoux C, Vukusic S, Mikaeloff Y, Edan G. Natural history of multiple sclerosis with childhood onset. N Engl J Med 2007. 356(25): p. 2603-2613. 18. Ness JM, Chabas D, Sadovnick AD, Pohl D, Banwell B, Weinstock-Guttman B. Clinical features of children and adolescents with multiple sclerosis. Neurology 2007; 68(16 suppl 2):S37-S45. 19. Etemadifar M, Janghorbani M,Shaygannejad V, Ashtari F . Prevalence of multiple sclerosis in Isfahan. Iran. Neuroepidemiology 2006; 27(1):39-44 (In Persian). 20. Saadatnia M, Etemadifar M, Maghzi AH. Multiple sclerosis in Isfahan, Iran. Int Rev Neurobiol 2007; 79: 357-75. 21. Nabavi SM, Poorfarzam S, Ghassemi H. Clinical Course and prognosis of 203 patients with MS in shahid Mostafa Khomeini Hospital, Tehran 2002, Tehran University Medical Journal, 200l 64( 7)6: 90-97.